Perlindungan Hukum terhadap Mahasiswa Peserta Program Pemagangan Pada Perusahaan Start-Up Dihubungkan Dengan Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2020 tentang Penyelenggaraan Pemagangan di Dalam Negeri dan Kitab Undang-Undang Hukum Perdata - Diana Marchella; Holyness N Singadimedja; Agus Suwandono (Universitas Sains dan Teknologi Komputer, 2024)
Nowadays, student internship programs are increasingly being held by start-up companies. However, in practice there are still many students participating in internships who have not received their rights as agreed in the internship agreement. Apart from that, there is no clear regulation regarding student internship programs in labor regulations in Indonesia, especially in Law of the Republic of Indonesia no. 6 of 2003 concerning Employment and Regulation of the Minister of Manpower of the Republic of Indonesia Number 6 of 2020 concerning the Implementation of Domestic Apprenticeships. This research aims to analyze the legal relationship between student interns and start-up companies and to find appropriate legal protection for student interns to defend their rights. This research was written using a normative juridical approach. The research results show that there is no employment law relationship between student interns and start-up companies. The legal relationship that occurs is a legal relationship that arises because of an internship agreement which is civil in nature and is subject to the Civil Code agreement law. Intern students whose rights are not fulfilled can seek repressive legal protection to defend their rights through non-litigation dispute resolution through negotiation. If non-litigation efforts are not achieved, litigation efforts can be pursued by filing a lawsuit, with the basis of the lawsuit being default and prioritizing mediation efforts in court first.